This preview shows pages 1–6. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: CHAPTER 6 LINEAR TRANSFORMATIONS 6.1 WHAT IS A LINEAR TRANSFORMA TION? You know what a function is  it’s a RULE which turns NUMBERS INTO OTHER NUMBERS: f ( x ) = x 2 means “please turn 3 into 9, 12 into 144 and so on”. Similarly a TRANSFORMATION is a rule which turns VECTORS into other VECTORS. For exam ple, “please rotate all 3dimensional vectors through an angle of 90 ◦ clockwise around the zaxis”. A LIN EAR TRANSFORMATION T is one that ALSO satisfies these rules: if c is any scalar, and * u and * v are vectors, then T ( c * u ) = cT ( * u ) and T ( * u + * v ) = T ( * u ) + T ( * v ) . 1 EXAMPLE : Let I be the rule I * u = * u for all * u . You can check that I is linear! Called IDENTITY Linear Transformation. EXAMPLE : Let D be the rule D * u = 2 * u for all * u . D ( c * u ) = 2( c * u ) = c (2 * u ) = cD * u D ( * u + * v ) = 2( * u + * v ) = 2 * u + 2 * v = D * u + D * v → LINEAR! Note: Usually we write D ( * u ) as just D * u . 6.2. THE BASIC BOX, AND THE MATRIX OF A LINEAR TRANSFORMATION The usual vectors ˆ i and ˆ j define a square: Let’s call this the BASIC BOX in two dimensions. 2 Similarly, ˆ i, ˆ j , and ˆ k define the BASIC BOX in 3 dimensions. Now let T be any linear transformation. You know that any 2dimensional vector can be written as a ˆ i + b ˆ j , for some numbers a and b . So for any vector, we have T ( a ˆ i + b ˆ j ) = aT ˆ i + bT ˆ j. This formula tells us something very important: IF I KNOW WHAT T DOES TO ˆ i and ˆ j , THEN I KNOW EVERYTHING ABOUT T because now I can tell you what T does to ANY vector. EXAMPLE : Suppose I know that T ( ˆ i ) = ˆ i + 1 4 ˆ j and T ( ˆ j ) = 1 4 ˆ i + ˆ j . Then what is T (2 ˆ i + 3 ˆ j )? Answer : T (2 ˆ i + 3 ˆ j ) = 2 T ˆ i + 3 T ˆ j = 2 ‡ ˆ i + 1 4 ˆ j · + 3 ‡ 1 4 ˆ i + ˆ j · = 2 ˆ i + 1 2 ˆ j + 3 4 ˆ i + 3 ˆ j = 11 4 ˆ i + 7 2 ˆ j . Since T ˆ i and T ˆ j tell me everything I need to know, 3 this means that I can tell you everything about T by telling you WHAT IT DOES TO THE BASIC BOX. EXAMPLE : Let T be the same transformation as above, T ( ˆ i ) = ˆ i + 1 4 ˆ j and T ( ˆ j ) = 1 4 ˆ i + ˆ j . The basic box has been squashed a bit! Pictures of WHAT T DOES TO THE BASIC BOX tell us everything about T ! EXAMPLE : If D is the transformation D * u = 2 * u , then the Basic Box just gets stretched: So every LT can be pictured by seeing what it does to the Basic Box. There is another way! Let T ˆ i = • a c ‚ and T ˆ j = • b d ‚ . Then we DEFINE 4 THE MATRIX OF T RELATIVE TO ˆ i, ˆ j as • a b c d ‚ , that is, the first COLUMN tells us what happened to ˆ i , and the second column tells us what happened to ˆ j ....
View Full
Document
 Spring '08
 McNines
 Transformations

Click to edit the document details